The role of language in discipline in improving academic english competence of interdisciplinary students - Tampubolon, Marlina; Rakasiwi, Rani; Silalahi, Masriani Mery Rosmida; Siahaan, Ricky Asi Erwindo (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Language plays a crucial role in academic and professional communication, particularly due to the diverse terminology used across different disciplines. Variations in the meaning of vocabulary in fields such as law, science, economics, and maritime studies often create ambiguity, especially for learners of academic English. This study aims to analyze how the meaning of English vocabulary shifts based on disciplinary context. Employing a qualitative descriptive method, data were collected through literature review and document analysis. The findings reveal that a single English word can hold different meanings depending on the field in which it is used—for instance, the word “sentence” generally refers to a linguistic unit, whereas in legal discourse, it denotes a judicial punishment. These results underscore the significant influence of disciplinary context on vocabulary interpretation and usage. The study highlights the importance of contextual language understanding to improve academic literacy and English proficiency among interdisciplinary students and professionals. Furthermore, the findings contribute to the development of discipline-specific academic English curricula and offer practical guidance for more effective English language teaching and learning.